Tips for Buildings Energy Saving: Results of Some Research - Roberto Sebastiano Faranda; Kim Fumagalli; Francesca Oliva (Energies, 2023)
Increasing global warming is largely attributable to human activities. International strategies have already been implemented to reduce emissions to zero, thus reducing energy consumption. Given the current world situation and the rising costs of raw materials (gas and oil), it is incumbent on us to find savings solutions that can also be implemented in our own small way; there are many solutions, especially in the domestic sphere. In this paper, the focus is on building energy savings that can be achieved using modern technologies and starting with the simplest solutions. In particular, this paper shows how the conscious use of natural lighting can lead to significant electricity savings. Moreover, it describes the effect of innovative building insulation materials and the effect due to the installation of a local photovoltaic power generation system; at the end, it illustrates the new horizons that are opening with the introduction of new building control techniques. Some studies are also reported where the extent of achievable savings can be understood.